Introduction to communication electronic warfare systems - Poisel, Richard (Artech House information warfare library., 2002)
Annotation This comprehensive engineering-level resource provides you with an excellent introduction to electronic warfare (EW) for communication systems. Extensively referenced with over 600 equations, it details the components, systems, and operations of electronic warfare systems dedicated to protecting and attacking military communications networks. You are provided with a complete understanding of how modern direction finders for communication signals work, along with their limitations.